1134 IN-HOSPITAL ARRHYTHMIC BURDEN REDUCTION IN DIABETIC PATIENTS WITH ACUTE MYOCARDIAL INFARCTION TREATED WITH SGLT2-INHIBITORS: INSIGHTS FROM THE SGLT2-I AMI PROTECT STUDY. (15th December 2022) - Cesaro, Arturo; Gragnano, Felice; Paolisso, Pasquale; Bergamaschi, Luca; Gallinoro, Emanuele; Sardu, Celestino; Mileva, Niya; Foà, Alberto; Armilotta, Matteo; Sansonetti, Angelo; Amicone, Sara; Impellizzeri, Andrea; et al.
Abstract: Background: Sodium-glucose co-transporter 2 inhibitors (SGLT2-i) have shown significant cardiovascular benefits in patients with and without type 2 diabetes mellitus (T2DM). They have also gained interest for their potential anti-arrhythmic role and their ability to reduce the occurrence of atrial fibrillation (AF) and ventricular arrhythmias (VAs) in T2DM and heart failure patients. Objectives: To investigate in-hospital new-onset cardiac arrhythmias in a cohort of T2DM patients presenting with acute myocardial infarction (AMI) treated with SGLT2-i vs. other oral anti-diabetic agents (non-SGLT2-i users). Methods: Patients from the SGLT2-I AMI PROTECT registry (NCT05261867) were stratified according to the use of SGLT2-i before admission for AMI, divided into SGLT2-i users vs. non SGLT2-i users. In-hospital outcomes included the occurrence of in-hospital new-onset cardiac arrhythmias (NOCAs), defined as a composite of new-onset AF and sustained new-onset ventricular tachycardia (VT) and/or ventricular fibrillation (VF) during hospitalization. Results: The study population comprised 646 AMI patients categorized into SGLT2-i users (111 patients) and non-SGLT2-i users (535 patients). SGLT2-I users had a lower rate of NOCAs compared with non-SGLT2-i users (6.3 vs.15.7%, p=0.010). Moreover, SGLT2-i was associated with a lower rate of AF and VT/VF considered individually (p = 0.032). In the multivariate logistic regression model, after adjusting for all confounding factors, the use of SGLT2-i was identified as an independent predictor of the lower occurrence of NOCAs (OR=0.35; 95%CI 0.14–0.86; p = 0.022). At multinomial logistic regression, after adjusting for potential confounders, SGLT2-I therapy remained an independent predictor of VT/VF occurrence (OR=0.20; 95%CI 0.04–0.97; p = 0.046) but not of AF occurrence. Conclusions: In T2DM patients, the use of SGLT2-i was associated with a lower risk of new-onset arrhythmic events during hospitalization for AMI. In particular, the primary effect was expressed in the reduction of VAs. These findings emphasize the cardioprotective effects of SGLT2-i in the setting of AMI beyond glycemic control. Trial registration: Data are part of the observational international registry: SGLT2-I AMI PROTECT. ClinicalTrials.gov Identifier: NCT05261867.